Effects of propolis on diabetes mellitus in SD rats - HU Fu-liang; XUAN Hong-zhuan; CHEN Min-li; YING Hua-zhong; ZHU Wei (浙江大学学报. 农业与生命科学版)
The effects of ethanol extracted propolis (EEP) and water soluble derivative of propolis (WSP) on diabetes mellitus in SD rats were determined and compared. The results showed that both WSP and EEP decreased levels of fasting blood glucose (FBG), glycosylated hemoglobin (HBAlc), fructosamine (FRU), triglyceride (TG), total cholesterol (TC), creatinine (CREA), blood urea nitrogen (BUN), uric acid (UA), malodialdehyde (MDA), total protein (TP) and albumin (ALB), and decreased the ratio of kidney to body weight in rats with diabetes mellitus. The results indicate that both EEP and WSP improved metabolism of glucose, fat and protein and afforded renal protection for rats with diabetes mellitus.